A Qualitative Study of Stakeholders’ Views on Pharmacovigilance System, Policy, and Coordination in Pakistan - Khan, Muhammad Akhtar Abbas; Hamid, Saima; Khan, Shahzad Ali; Sarfraz, Mariyam; Babar, Zaheer-Ud-Din (Frontiers in Pharmacology, 2022)
Objectives: Due to the absence of necessary rules, poor coordination, and various challenges, the pharmacovigilance system of Pakistan is not optimally functional at all levels of the health system. The objective of the study was to assess the stakeholders’ perceptions of the current ADR reporting system and to identify the pharmacovigilance policy issues, and problems of effective coordination. Methodology: Stakeholders from a broad range of disciplines, academia, regulatory authorities, the pharmaceutical industry, international health organizations, as well as pharmacovigilance experts and healthcare professionals were included in the study. A total of 25 stakeholders throughout Pakistan were interviewed during exploratory semi-structured interviews. The interviews were recorded digitally, transcribed, coded, compared, and grouped according to their similarity of themes. Participants provided insights into gaps, limitations, and challenges of Pakistan's current ADR reporting system, issues with proposed pharmacovigilance rules, and coordination difficulties. Results: The majority of the participants considered the ADR reporting system in Pakistan to be improving but in a nascent phase. The identified gaps, challenges, limitations of the system, and barriers to reporting were labeled as reasons for limited functioning. Almost all stakeholders were aware of the existence of draft pharmacovigilance rules; however, participants in the industry were familiar with the contents and context of draft pharmacovigilance rules. Bureaucratic red tape and lack of political will appeared to be the top reasons for delaying the approval of the pharmacovigilance rules. Wider consultation, advocacy, and awareness sessions of policymakers and HCPs were suggested for early approval of rules. Participants unanimously agreed that the approval of rules shall improve the quality of life and reduce the economic burden along with morbidity and mortality rates. The need for greater and collaborative coordination among the stakeholders in promoting medicines' safety was highlighted. All participants suggested the use of media, and celebrities to disseminate the safety information. Conclusion: Participants showed partial satisfaction with the way pharmacovigilance in Pakistan is moving forward. However, stakeholders believed that engagement of multi-stakeholders, approval of pharmacovigilance rules, and the establishment of pharmacovigilance centers in provinces, hospitals, and public health programs (PHPs) shall support to achieve the desired results.